Model Probing-Prompting Learning Pada Pembabelajaran Materi Rambu-Rambu Lalu Lintas Kelas III Sekolah Dasar - Hikmatul Ghina; Larasati Dewi; Prihartini Prihartini (Universitas Palan, 2024)
Learning about traffic signs has been carried out since elementary school level. The right learning model will certainly make it easier for students to absorb the material and make it easier for students to understand and remember it. The Probing Prompting learning model is a learning model that can be applied to traffic sign material. This article uses a descriptive method with literature study techniques.